Preparation and microstructure characterization of W–0.1 wt.%TiC alloy via chemical method. (February 2016) - Lang, Shaoting; Yan, Qingzhi; Wang, Yijia; Zhang, Xiaoxin; Sun, Ningbo; Deng, Lin; Ge, Changchun
Abstract: W–0.1 wt.%TiC materials with and without the addition of PVP were fabricated by wet-chemical method and spark plasma sintering. The microstructures were characterized by FESEM and TEM. The results revealed that the addition of PVP remarkably improved the uniform dispersion of TiC particles during the synthesis process. W–TiC without PVP showed dispersoids with size of 100–1000 nm were distributed unevenly in the tungsten matrix; only a few particles with the size of about 80–300 nm were located in tungsten grain interior. Conversely, the microstructure of W–TiC with PVP showed that dispersoids were dispersed well and kept about 80 nm. Moreover, the majority of them were uniformly distributed in the grain interior. The EDS analyses revealed that the dispersoids were composed of Ti, C, O and W. TEM observations further verified that the dispersoids were TiC particles. W–TiC with PVP showed better mechanical properties when compared with the samples of W–TiC without PVP and pure tungsten. Graphical abstract: W–0.1 wt.%TiC materials with and without the addition of PVP were fabricated by wet-chemical method and spark plasma sintering. By adding PVP during the dispersing process, the TiC particles were finer and more uniformly distributed in the tungsten matrix with a high share in the grain interior after sintering. Highlights: W-0.1wt.%TiC with nano TiC particles uniformly distributed in grain interior were fabricated by wet-chemical method. The addition of PVP can remarkably improve the uniform dispersion of nano TiC particles in the sintered microstructure. W-TiC with PVP showed improved mechanical properties than the samples sintered without PVP and pure tungsten.